Child Labour in Indonesia: Supply-Side Determinants - Haszelinna binti Abang Ali, Dayang; Arabsheibani, G. Reza (UI Scholars Hub, 2016)
This study analyses the determinants of working among 10-17 years children and to investigate the presence of Luxury Axiom. Child tends to work as they gets older, has biological ties to the household head and lives in a rural area. The higher levels of household heads education lead to the childrens been less likely to work. With regard to the Luxury Axiom, household income is negatively impact the work decision. Birth order is positively related to working and the probability of working decreases by the presence of employed adult. Finally, the impact of the childs activities varies by provinces.